Macrobenthic functional group analysis of ecological health of the intertidal artificial oyster reefs in the Yangtze Estuary, China - Zhang, Yinan; Wan, Hang; Zhao, Yunlong; Ding, Jiafeng; Zhu, Zhenchang; Zhang, Hangjun; Liu, Zhiquan (Frontiers in Marine Science, 2023)
The functional groups and the ecological health of a constructed oyster reef were investigated during April 2016 to October 2017 in the Yangtze estuary. The data of the long-term monitoring program (14 years) confirmed the feasibility of creating an artificial oyster reef in Yangtze estuary. One or two functional groups were absent from moderate salinity conditions (5.17% - 8.73%), while macrobenthos functional group species richness, abundance, and biomass were greatest under high salinity conditions. The feeding evenness index (jFD) showed that 14 years after construction, the ecosystem health of the artificial oyster reefs were good or high, and was better under high salinity conditions. Ecological health was lower under moderate levels of salinity, possibly due to the absence of some functional groups. Redundancy analysis indicated ecosystem health was associated with changes in salinity and substrate factors. Our study confirmed artificial oyster reef construction is feasible and has a positive effect on estuarine ecosystem health.